Advanced bile acid-based multi-compartmental microencapsulated pancreatic ß-cells integrating a polyelectrolyte-bile acid formulation, for diabetes treatment. - Mooranian, A.; Negrulj, R.; Chen-Tan, N.; Fakhoury, M.; Arfuso, F.; Jones, Franca; Al-Salami, H. (2014)
This study utilized the Seahorse Analyzer to examine the effect of the bile acid ursodeoxycholic acid (UDCA), on the morphology, swelling, stability, and size of novel microencapsulated ß-cells, in real-time. UDCA was conjugated with fluorescent compounds, and its partitioning within the microcapsules was examined using confocal microscopy. UDCA produced microcapsules with good morphology, better mechanical strength (p < 0.01), and reduced swelling properties (p < 0.01), but lower cell viability (p < 0.05) and cell count per microcapsule (p < 0.01). UDCA reduced the cells' biochemical activities, mitochondrial respiration, and energy production, post-microencapsulation. This is the first time biological functions of microencapsulated ß-cells have been analyzed in real-time.